Local Wisdom and Relational Supervision in Educational Human Resource Management: Insights from Teacher Competency Practices - Nurdiana Nurdiana; Joko Sutarto; Wasino Wasino; Tri Joko Tri Joko Raharjo; Ahmad Hariyadi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to examine how local wisdom values are interpreted and practiced in educational supervision and their contribution to teacher competency development in schools. The study used a multi-site qualitative case study design involving 12 participants. Data were collected through in-depth interviews, participant observation, and document analysis. Data analysis was conducted thematically to identify relational, ethical, cultural, and spiritual patterns in supervisory practices. The results show that supervision is not only understood as an administrative control mechanism but also as a dialogic process built through deliberation, cooperation, trust, respect, and communal solidarity. These values contribute to a more open, reflective, and collaborative professional relationship between teachers, principals, and supervisors. The results of this study expand the study of educational supervision by demonstrating the importance of ethical and relational dimensions based on local wisdom in the practice of supervising educational human resources. This research has implications for educational supervision policies that need to integrate local wisdom values beyond administrative aspects. In school practice, supervision is directed to be dialogic, collaborative, and trust-based. This improves teacher competency holistically by strengthening pedagogical, social, and ethical aspects, thereby creating a more humane and sustainable educational ecosystem.